Efficacy of autologous whole blood or serum therapy for chronic spontaneous urticaria: a systematic review and meta-analysis. (17th November 2019) - Chang, Hua-Ching; Sung, Chih-Wei; Lin, Ming-Hsiu
Abstract: Background: Chronic spontaneous urticaria (CSU) is chronic wheals without identifiable exogenous stimuli. Autologous whole blood (AWB) injection and autologous serum therapy (AST) are alternative therapies for CSU that induce tolerance to circulating histamine-releasing factors. Objective: We elucidated currently available evidence for the efficacy and safety of AWB therapy and AST for CSU. Methods: We systematically searched four databases for eligible studies to perform meta-analysis. The primary outcome was the efficacy of AST or AWB therapy, and the secondary outcome was improvement after intervention based on the autologous serum skin test (ASST) status of patients. Results: Eight clinical trials, including four randomized controlled trials and 529 CSU patients, were identified. AST was not more effective than the placebo treatment in alleviating CSU symptoms at the end of treatment ( p  = .161), and AWB injection was also not more effective in response rates than the placebo at the end of follow-up ( p  = .099). Furthermore, the efficacy of AST or AWB injection for CSU and the ASST status were not significantly related. No remarkable adverse events were recorded during therapy. Conclusions: Our meta-analysis suggested that AWB therapy and AST are not significantly more effective in alleviating CSU symptoms than the placebo treatment.